Kartun untuk Periklanan: Studi Kasus Desain Kartun Koyoiki Design Studio - Muttaqien, Muhammad; Muktaf, Zein Mufarrih (Universitas Muhammdiyah Yogyakarta, 2025)
Cartoons are visual works that are predominantly used in advertising works, such as logos, mascots, illustrations, comics, and even animations. Cartoons are creative works that involve an imaginative creative visual process. This study is a study of the creative process of making cartoons for advertising. Koyoiki Design Studio is a design studio that produces a lot of cartoon production works for mascots, logos, or advertisements. This study wants to see how the process of making cartoon works at Koyoiki Design Studio. The method used is a case study approach. The reason for using this approach is to obtain information about the process that occurs at the creative stage of making cartoon characters. The novelty in this study is; first, cartoon design is straightforward and flexible. Visually, cartoons are not realistic, and are more directed at funny visuals, although this does not mean that funny visuals are intended for funny needs. Second, Cartoons are simple and directed at symbolic forms. Commercial cartoons tend to follow general cartoon rules, such as bright colors, funny, interesting and imaginative. Because commercial cartoon design considers audience acceptance. Third, Cartoons consider propositions. Cartoons often involve associations or personifications, so that the audience understands what the character means. The role of cartoons consists of a). Design Thinking and Brief Analysis, b). Collection of references, c). Selection of objects to display cartoons, d). Managing objects into cartoon characters.